(untitled) (Global Journal of Medical Research, 2016)
The intertrochanteric fractures cause, over variable degrees, many problems of management problems of taking depending on the physiological condition of the patient as well as diseases that are associated. The literature is rich in studies on per trochanteric fractures. The results of treatment of intertrochanteric fractures were changed by the emergence of resistant osteosynthesis implants, avoiding certain mechanical failures, also by raising awareness of pre and post operative care and reducing very significantly the level of postoperative mortality at the origin of the bad reputation of these fractures in the elderly. The occurrence of contralateral trochanteric fracture is a rare and unusual event reported in the literature. A retrospective study is reported in 24 patients with a mean age of 68 years with bilateral trochanteric fracture. An analysis of the epidemiological distribution of morbidity and mortality has been made with a description of the postoperative evolution and functional outcome in these patients.